2009
DOI: 10.1016/j.disc.2007.12.092
|View full text |Cite
|
Sign up to set email alerts
|

A realization of graph associahedra

Abstract: Given any finite graph G, we offer a simple realization of the graph-associahedron PG using integer coordinates.2000 Mathematics Subject Classification. Primary 52B11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 12 publications
0
70
0
Order By: Relevance
“…Devadoss et al [8] showed how to convexify star-shaped polygons by moving all the vertices in the polygon simultaneously. We believe that our techniques should extend to star-shaped polygons, but so far we have not been able to do it.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Devadoss et al [8] showed how to convexify star-shaped polygons by moving all the vertices in the polygon simultaneously. We believe that our techniques should extend to star-shaped polygons, but so far we have not been able to do it.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
“…On the other hand, we give an example that shows that the answer to Question (1) is negative, even for monotone polygons. For recent results on this topic, see also [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(equivalently: does every polygon admit a visibility-preserving convexification?) Devadoss [5] also raised a stronger version of this question: (2) does there exist a visibility-preserving convexification in which at most one vertex is moved at a time (that is, by singlevertex moves)? Partial answers to (1) and (2) were given in [2] and [5].…”
Section: Introductionmentioning
confidence: 99%